カイリョウガタ ヒョウショウ シンソウ クッサク ドリル ノ ソウゴウ ジッケン ホウコク -2002ネン ホッカイドウ リクベツチョウ デノ ジッケン- - 亀田, 貴雄; カメダ, タカオ; 藤井, 理行; フジイ, ヨシユキ; 高橋, 昭好; タカハシ, アキヨシ; 田中, 洋一; タナカ, ヨウイチ; 成田, 英器; ナリタ, ヒデキ; 新堀, 邦夫; シンボリ, クニオ; et al. (国立極地研究所, 2002)
P(論文) 2003/2004年からは, 第二期ドームふじ観測計画として, 3028mの氷床底部までの深層掘削が予定されている。この計画のために, 我々は新たに改良型氷床深層掘削ドリル(全長12.2m, 最大採取コア長3.8m)を開発し, 2002年1月末から2月にかけて北海道陸別町において総合掘削実験を実施した。本論文ではこの実験の概要と結果を述べる。実験の結果, 3つのスクリュー(直径112mm, 長さ100mm)をチップ室につけ, 切削刃のピッチを5mmに調整すると, 安定した掘削能力があることがわかった。また, チップ室側面に多数の孔(直径1.2mm, 総数約45000)を開けることで掘削中の液流循環が確保され, 3.8m長のコアを掘削することに役だった。チップの乾き密度は440-500kg/m^3であり, 掘削時のチップ回収率は65-91%であった。切削終了後に液中でバレルを空転させる時間が長い場合や切削ピッチが2の場合は, チップ回収率が高くなる傾向にあった。チップ逆流防止弁は, 充分な実験ができなかったが, 今後さらに高耐久仕様にすることが望まれる。新たに開発した駆動ユニットやコアキャッチャーも正常に動作した。平均掘削速度(刃先をピッチ5mmにした場合)は24.5cm/min, 掘削中の平均消費電力は, 171Wであった。 Deep ice coring to bedrock (3028m in depth) at Dome Fuji Station is planned during three successive summer seasons starting from 2003/2004. An improved JARE deep ice core drill (12.2m in length and 3.8m in maximum core length) was developed in December 2001 for the ice coring at Dome Fuji. In January/February of 2002,we performed experiments on drill performance using artificial ice blocks in Rikubetsu, Hokkaido. In this paper, we outline the experiment and report the results. It was found through the experiment that an ice core of 3.8m length was smoothly obtained by the improved drill with three screws in the chip chamber and cutting pitch of 5mm/cycle. About 45000 small holes 1.2mm in diameter were made on the surface of the chip chamber. These small holes enabled liquid to circulate between cutters and outside of the drill through the chip chamber in the drill. The dry density of the chips was 440 to 500kg/m^3 and the chip recovery rate during ice coring was 65 to 91%. A check valve installed at the bottom of the chip chamber to prevent outflow of chips from the drill was not tested enough, but more durability is needed for the valve. The newly developed motor system and core catchers of the drill worked perfectly. The average coring speed was 24.5cm/min with cutting pitch of 5mm/cycle. The average power consumption during ice coring was 171W. departmental bulletin paper